Features of E-Learning of Personnel in Small and Medium-Sized Businesses - A. A. Paskova (Цифровая трансформация, 2019)
Small and medium-sized enterprises provide economic growth in many countries of the world. Economic pressure requires continuous improvement of the company's efficiency, staff knowledge, training to survive or remain competitive. Due to limited resources, often financial, SME managers reduce training activities and the introduction of new technologies in their companies.The purpose of this article was to study the possibilities of e-learning in SMEs. The main trends of modern e-learning were considered.It was noted that, despite the obvious advantages of using e-learning in SMEs, there were a number of obstacles to the active introduction of e-learning, namely: lack of availability of e-learning, lack of management support, lack of quality courses, reluctance of staff to use technology, lack of investment by companies in technology and lack of University-level and non-academic courses tailored to the needs of the enterprise.The article considers possible ways of overcoming the described problems and suggests ways to solve them.